ORNAMENTS AS A SYNTHESIS OF ARTS IN LANDSCAPE DESIGN OF UZBEKISTAN CITIES - Mirpulatova Munis Akmal Kizi. , Aliyeva Manzura Hamidilla kizi , Komiljonov Muhammadsolikh Sobirjon ugli , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article analyzes the possibility of using ornaments in the landscape design of cities in Uzbekistan. Ornaments of architectural decor of the most ancient cities of Uzbekistan, Islamic ornaments, ornaments of traditional decorative applied art of Uzbekistan are considered as sources for the search for new artistic solutions in landscape art. The conceptual use of ornament in the landscape, as a planning structure and art objects for landscape gardening design is highlighted. The importance of the role of studying ornament as an artistic image and synthesis of arts in design in the training of environmental designers is noted.